2019
DOI: 10.1111/1744-7917.12702
|View full text |Cite
|
Sign up to set email alerts
|

BmSd gene regulates the silkworm wing size by affecting the Hippo pathway

Abstract: Insect wings are developed from the wing disc during metamorphosis. Bombyx mori, a model lepidopteran insect, loses flight ability after long-term domestication from the wild silkworm, Bombyx mandarina. The mw mutant (u11 strain) shows minute wings compared to wild type (e.g., p50 strain) wings. RNA sequencing analysis previously revealed differential Hippo-pathway-related gene expression between the u11 and p50 strains. The Hippo pathway is an evolutionarily conserved signaling cascade that controls organ siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…The KEGG analysis showed that 209 and 211 KEGG pathways were successfully annotated in G. licenti and M. japonicus, respectively. And among which Wnt, Notch, Hedgehog, Hippo and other pathways played critical roles in insect growth and development, for example, the Wnt signaling pathway has been shown to be essential for both embryogenesis and organogenesis, such as controlling axis elongation and leg development of one short-germ insect 63 , and the Hippo signaling pathway is an evolutionally-conserved signaling cascade that plays a role in controlling organ size during animal development, such as controlling the size of silkworm wings 64 . GO annotations are classified into three main categories: biological process, cellular component and molecular function.…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG analysis showed that 209 and 211 KEGG pathways were successfully annotated in G. licenti and M. japonicus, respectively. And among which Wnt, Notch, Hedgehog, Hippo and other pathways played critical roles in insect growth and development, for example, the Wnt signaling pathway has been shown to be essential for both embryogenesis and organogenesis, such as controlling axis elongation and leg development of one short-germ insect 63 , and the Hippo signaling pathway is an evolutionally-conserved signaling cascade that plays a role in controlling organ size during animal development, such as controlling the size of silkworm wings 64 . GO annotations are classified into three main categories: biological process, cellular component and molecular function.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the RNAi effect, two specific small interfering RNAs (siRNAs) targeting different Bmcas‐1 domains were designed following the previously reported method (Yin et al, 2019). The siRNA oligos used to synthesize siRNA were synthesized by SUNYA Biotechnology (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…To knockdown the expression of Bmapaf-1 in BmN cells, two specific siRNAs targeting sequences located in the functional domain of Bmapaf-1 were selected and designed using the method in a previous study [ 23 ]. The target DNA sequence was inserted behind the T7 promoter, and the siRNA oligos were synthesized by SUNYA Biotechnology (Zhejiang, China; Table 2 ).…”
Section: Methodsmentioning
confidence: 99%